Efeitos de diferentes regimes de fogo na comunidade de formigas do cerrado - Maravalhas, Jonas (2013)
Disturbance has been increasingly recognized as a structuring force in nature. Fire is an important feature of many xeric and seasonal ecosystems, where it maintains habitat structure and allows the persistence of local populations. The Cerrado is a Neotropical savanna characterized by frequent burning, but changes in the fire regime threaten the conservation of this biome. Exclusion of fire causes a shift in vegetation, benefitting trees and eventually resulting in a forest. Intensification of fires benefits grasses, and can be detrimental to Cerrado organisms adapted to the natural fire regime. The development of appropriate fire management strategies is essential, but this task is hindered by the lack of scientific information on the effects of fire on Cerrado organisms. Ants are ubiquitous in tropical ecosystems and are responsive to changes in the habitat, thus ideal for studying disturbance impacts. We assessed how the ant community changed between fire regimes in a Cerrado of Central Brazil. Fire treatments were maintained for 15 years over 150 ha of typical cerrado vegetation. Fire frequency effects were tested comparing plots subjected to fire suppression (C0) or mid-season fires every four (M4) or two years (M2). The latter was also compared to early-season (E2) and late-season (L2) plots, assessing the effects of the burning period. We used baited pitfall traps to collect ants from the soil (epigaeic) and vegetation (arboreal) in four blocks containing all five regime treatments. We evaluated changes in species richness and composition of the ant community and made parallels with changes in vegetation structure. Also, we compared the number of ant species among potential management strategies with varying levels of fire regime diversity and evaluated the contribution of fire diversity in overall ant diversity with additive partitioning. We collected a total of 165 ant species from 4,480 records. There was significantly less ant species in fire-suppressed sites, but among fire-treated sites, no difference was detected irrespective of frequency or period of burning. Meanwhile, community composition changed sharply between treatments, especially at fire frequency comparison, where both arboreal and epigaeic species composition changed between C0, M4 and M2 plots. Comparing period levels, though, there was a significant separation between E2, M2 and L2 plots only for epigaeic species. Contrasting potential management strategies, we found significantly more species when dissimilar fire regimes were combined, highlighting the importance of fire regime diversity in maximizing biological diversity. The results of the additive partition reinforce this idea, as 42% of the total diversity was due to turnover between fire treatments. Fire-suppressed sites support less ant species, nevertheless they are important to forest-associated species. High frequency fires, like M2 or L2, maintain the savanna structure and allow the persistence of open-habitat species. In this sense, we advocate for the use of prescribed burning in Cerrado preserved areas. Furthermore, an appropriate fire management should have some level of regime diversity in order to maintain habitat variability and maximize conservation of species.